PENERAPAN PENGETAHUAN KEPUTUSAN PEMBELIAN MAKANAN JAJANAN PADA MAHASISWA PRODI PENDIDIKAN TATA BOGA UPI - Siti Patimah, - (2020)
Students in general interested in snack because the taste is good, the price is cheap and the proximity do not pay attention to the criteria of good snacks. Students education of Tata Boga are provided with knowledge about Purchase Decisions. The purpose of this study was to obtain related information to the application of snack food purchase decisions to students education of Tata Boga UPI departement. This research method is analytic descriptive method. The population in this research is generation 2016 from students education of Tata Boga there was 62 people, with a sample of 53 people conducted in purposively. The results of this study are the purchasing decisions snack for students because the food is most preferred, because of good food, and food can eliminate hunger. Information obtained by students about snack food is more than half obtained from friends' experience. The suggestion from this research is that students read information on snacks from sources of books, newspapers, or magazines so that snacking is based on knowledge. Keywords: Implementation, food purchasing decisions, consumer education, UPI culinary education study program.